2015
DOI: 10.21836/pem20150501
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the pressure force distribution affecting the hoof and its influenceability by different ground properties

Abstract: Zusammenfassung: Erkrankungen des Hufes stellen beim Pferd eine stete Herausforderung dar. Ziel der vorliegenden Studie war die Untersuchung des Einflusses verschiedener Bodenbeschaffenheiten auf die dorsopalmare und mediolaterale Druckverteilung des Hufes. Der ausgeschnittene Huf der jeweils linken Vordergliedmaße von 25 Warmblutpferden wurde mithilfe eines folienbasierten Druckmesssystems auf unterschiedlichen Böden und im Schritt und Stand untersucht. Die hochflexiblen Sensoren wurden individuell der Huffor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Comparable effects were recently found by Hüppler et al [15] between concrete and soft floorings in standing and walking horses. In the present study, even differences between the tested rubber floorings in loaded area and overall pressure load could be observed.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Comparable effects were recently found by Hüppler et al [15] between concrete and soft floorings in standing and walking horses. In the present study, even differences between the tested rubber floorings in loaded area and overall pressure load could be observed.…”
Section: Discussionsupporting
confidence: 64%
“…It has frequently been used in equine research and was recommended for scientific and clinical application by Lange et al [17]. As some authors stated a lack of accuracy in using this piezoresistive foil sensors [19, 21, 31], most equine studies were confined to relative comparisons [14, 15, 17]. However, by use of an appropriate calibration under trial conditions and expected loads, an adequate accuracy could be obtained with this sensors [19–21].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed knowledge of the load distribution pattern within different hoof regions in horses with laminitis will help the equine practitioners to optimise the supportive therapy. The Hoof ™ System has been successfully used to evaluate the load distribution within the hoof in shod and unshod horses, and to study the effect of different horseshoes at different ground properties 8‐10 . However, no kinetic measurements have been performed to assess the load distribution in the laminitic hoof so far.…”
Section: Introductionmentioning
confidence: 99%
“…Placing the laminitic horses on sand or peat is beneficial in supporting the sole thus reducing the load on the hoof wall, as these substrates conform well to the foot [1]. It has been demonstrated that the contact area in clinically sound horses increases to almost double when on deep sand compared to a concrete surface [13]. Therefore, laminitic horses with HCHW would benefit from soft bedding due to increased contact area.…”
Section: Discussionmentioning
confidence: 99%